2018
DOI: 10.1159/000490669
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors and Molecular Mechanisms of Vitamin D and Obesity Relationship

Abstract: Vitamin D (vitD) deficiency is associated with a wide range of chronic diseases and conditions, including obesity, and with an increasing severity of metabolic dysregulation, such as insulin resistance, hyperlipidemia, liver disease, and hypertension, both in children and adults. However, the nature of the association between low vitD status and obesity remains unclear. This fact has motivated the scientific community to conduct genetic association analyses between 25-hydroxyvitamin D (25[OH]D)-related genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 72 publications
(93 reference statements)
2
82
0
5
Order By: Relevance
“…In our study, 70% of adolescents with obesity had baseline 25(OH)-D concentrations lower than 50 nmol/L (equal to 20 ng/mL), which defines deficiency according to the French guidelines [32]. Obesity-related VD insufficiency could be explained by many factors: sun underexposure, inadequate intake of VD-rich foods and beverages, genetic factors [33], sequestration of this fat-soluble vitamin, and its volumetric dilution [34] Our finding that 25(OH)D levels as total and free were increased also in the ONS group after the 3-month lifestyle program suggests a possible release of VD during weight loss in the absence of VD supplementation. Previous studies also reported increased circulating 25(OH)D levels in adults with obesity after adiposity loss through lifestyle interventions without VD supplementation [14].…”
Section: Discussionmentioning
confidence: 86%
“…In our study, 70% of adolescents with obesity had baseline 25(OH)-D concentrations lower than 50 nmol/L (equal to 20 ng/mL), which defines deficiency according to the French guidelines [32]. Obesity-related VD insufficiency could be explained by many factors: sun underexposure, inadequate intake of VD-rich foods and beverages, genetic factors [33], sequestration of this fat-soluble vitamin, and its volumetric dilution [34] Our finding that 25(OH)D levels as total and free were increased also in the ONS group after the 3-month lifestyle program suggests a possible release of VD during weight loss in the absence of VD supplementation. Previous studies also reported increased circulating 25(OH)D levels in adults with obesity after adiposity loss through lifestyle interventions without VD supplementation [14].…”
Section: Discussionmentioning
confidence: 86%
“…Vitamin D is important in a wide range of physiological processes, and its deficit has been related to different chronic diseases and metabolic conditions, including obesity. Nonetheless, encompassing literature studies indicated only a faint association between gene variants acting in vitamin D metabolism and the obese phenotype [33], while the environment seems to play a major role [34][35][36]. The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to the six susceptibility loci harboring genome-wide significant SNPs (recently identified in a large GWAS) is 7.5%, with statistically significant loci explaining 38% of this total [37].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports that these VDR polymorphisms are associated with T2DM and insulin secretion [19][20][21]. In addition, VDR polymorphisms are related to metabolic syndrome, metabolic changes related to obesity [22]. The association of the VDR gene polymorphisms and T2DM in older people living in a community of Santiago de Chile, Chile, were previously established through a case-control study on 138 T2DM patients and 172 control subjects with ages ranging from 60-79 years.…”
Section: Discussionmentioning
confidence: 99%